PEMBELAJARAN KOSAKATA BAHASA JEPANG TINGKAT DASAR DENGAN MENGGUNAKAN MEDIA RIDDLE GOI - Fajar Achmad Fardyaz; Soni Mulyawan Setiana (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
This study aims to find out how to make Riddle Goi media. This study uses the ADDIE method. This media contains Japanese and Indonesian vocabulary sentences contained in the book Easy and Practical Success Tips for Reaching N5, in this media there are also exercises that can be used to practice memorized vocabulary. Making Riddle Goi media using Adobe Flash CS6 as software in the manufacturing process. The results of this study will produce Riddle Goi learning media for learning Japanese vocabulary. The author hopes that this application can make it easier for people to learn or memorize Japanese vocabulary.